PERANCANGAN HYBRID SOLAR HOME SYSTEM MENGGUNAKAN GRID TIE INVERTER - Pratama, Renaldi Putra; Zainuri, Akhmad; Nurussa’adah, n/a (Jurnal Mahasiswa TEUB, 2024)
Energy is a basic necessity for society in any country, including Indonesia. The rapid population growth in Indonesia has led to an increase in energy usage across various sectors such as agriculture, education, healthcare, transportation, and the economy. The reliance on non-renewable energy is becoming increasingly concerning, necessitating the utilization of renewable energy sources. One of the solutions that can be adopted is the Solar Power Plant or Solar Home System (SHS). This study designs an Automatic Transfer Switch (ATS) for switching between two power sources, PLN and Grid Tie Inverter (GTI), and designs a circuit to enablethe GTI to operate without being connected to the PLN grid. The SHS circuit using a GTI consists of an ATS and a trigger inverter or low-frequency inverter. The ATS uses two DPDT relays with a current capacity of 10A controlled by an Arduino Nano, equipped with a voltage detector, a zero crossing detector, and current and voltage modules. The low-frequency inverter uses a MOSFET switching circuit, a step-up transformer, and a voltage feedback circuit. The results of the study show that when the trigger inverter is active, the GTI is also active, indicated by a green light on the GTI. The switch from PLN to GTI occurs without delay andwithout waveform differences in the load, although there is a slight, insignificant voltage drop with a time interval of 61ms. This study successfully demonstrates that the ATS and GTI system can function as designed to support the availability of renewable energy in Indonesia. Keywords: SHS, Solar power plant, ATS, GTI.